BOARD DIVERSITY AND INTELLECTUAL CAPITAL ON COMPANY VALUE WITH PROFITABILITY AS INTERVENING VARIABLES - Muhammad Pondrinal; Ronni Andri Wijaya; Yosi Yulia; Mayroza Wiska (Lembaga Layanan Pendidikan Tinggi Wilayah X, 2022)
This study aims to determine the analysis of the effect of board diversity and intellectual capital on firm value with profitability as the case study intervening variable in manufacturing companies listed on the Indonesia Stock Exchange in 2016-2020. The sample in this study was taken by purposive sampling method on manufacturing companies listed on the Indonesia Stock Exchange in the 2016-2020 period. The number of samples used as many as 33 companies. The method of analysis of this research is to use the method of path analysis and hypothesis testing.The results of this study indicate that partially the effect of board diversity and intellectual capital has a significant positive effect on profitability, board diversity and intellectual capital have a positive and significant effect on firm value, while profitability has no significant effect on firm value in manufacturing companies listed on the Indonesia Stock Exchange in 2016-2020 years. In direct and indirect influence it is stated that board diversity has a significant effect on firm value mediated by profitability as an intervening variable and intellectual capital has a significant effect on firm value mediated by profitability as an intervening variable in manufacturing companies on the Indonesia Stock Exchange in the 2016-2020 period